Students and Teachers Using Mentimeter: Technological Innovation to Face the Challenges of the COVID-19 Pandemic and Post-Pandemic in Higher Education - J. Ignacio Pichardo; Esteban F. López-Medina; Olga Mancha-Cáceres; Isabel González-Enríquez; Alejandro Hernández-Melián; Maribel Blázquez-Rodríguez; Virginia Jiménez; Marina Logares; David Carabantes-Alarcon; Mónica Ramos-Toro; Esther Isorna; Mónica Cornejo-Valle; et al. (Education Sciences, 2021)
The COVID-19 pandemic has prompted higher university lecturers to develop their digital skills in order to adapt to online teaching. A group of university teachers decided to evaluate the educational uses of Mentimeter to promote student participation and active learning. A questionnaire was answered by 400 students and 12 participating academics. These 12 academic respondents also participated in a focus group after experiencing this software during an academic course. Qualitative and quantitative data was collected and analyzed to conclude that this software not only facilitated student participation during the pandemic (both face-to-face and online) in synchronous and asynchronous ways but also improved attention, engagement, collaborative learning and interaction. Immediate feedback made it possible for teachers to monitor the students’ learning processes and to adjust the content and pace accordingly. Students and educators highlighted the inclusive potential of this tool, as it allows participation from a diverse audience with different backgrounds and capacities, ensuring inclusive and equitable education for all. Some opportunities for improvement were also identified, namely more functions to make the software more attractive and adapt it to different educational objectives.